Q: What is 6x plus 3 equals 2x plus 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x

9

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

6x + 15

Related questions

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

2x+9=6x-3 Therefore 4x=12 -->x=3

x would be -3

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x

2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

common it's very easy !!2x + 3 = 92x = 6x = 6/2x = 3

6x - 3y = 6 y= 2x + 5 replace 2x + 5 for y into the first equation 6x - 3y = 6 6x - 3(2x + 5) = 6 6x - 6x - 15 = 6 0 - 15 = 6 -15 = 6 False So the system has no solution.

6x + 3 = 3(2x + 1)